Enzymatic production of pectic oligosaccharides from onion skins. (1st August 2016) - Babbar, Neha; Baldassarre, Stefania; Maesen, Miranda; Prandi, Barbara; Dejonghe, Winnie; Sforza, Stefano; Elst, Kathy
Highlights: Onion hulls are potential candidates for pectic oligosaccharide production. Enzyme EPG-M2 is able to produce pectic oligomers from onion hulls. The formation of DPs were influenced by enzyme concentration and contact time. Highest production of DP3 and DP2 were achieved using 5.2 IU/mL of EPG-M2. Highest production of longer DP4 were achieved using EPG-M2 (2.6 IU/g). Abstract: Onion skins are evaluated as a new raw material for the enzymatic production of pectic oligosaccharides (POS) with a targeted degree of polymerization (DP). The process is based on a two-stage process consisting of a chelator-based crude pectin extraction followed by a controlled enzymatic hydrolysis. Treatment of the extracted crude onion skin's pectin with various enzymes (EPG-M2, Viscozyme and Pectinase) shows that EPG-M2 is the most appropriate enzyme for tailored POS production. The experiments reveal that the highest amount of DP2 and DP3 is obtained at a time scale of 75–90 min with an EPG-M2 concentration of 26 IU/mL. At these conditions the production amounts 2.5–3.0% (w/w) d.m for DP2 and 5.5–5.6% (w/w) d.m for DP3 respectively. In contrast, maximum DP4 production of 5.2–5.5% (w/w) d.m. is obtained with 5.2 IU/mL at a time scale of 15–30 min. Detailed LC–MS analysis reveals the presence of more methylated oligomers compared to acetylated forms in the digests.